Tingkat Kepuasan Pasien BPJS dan Non BPJS terhadap Pelayanan Kesehatan - Marga, Irawati; Tjokro, Silvia Haniwijaya; Fajriyah, Novita (Journal of Health Management Research, 2022)
Background: Satisfactory health services are everyone's expectations, so the government makes policies with health insurance that are mutual cooperation by creating a National Health Insurance program and organized by the Social Security Administering Body. However, not all BPJS users get satisfaction with health services, as well as other insurance users. Aims: This study aims to compare the level of satisfaction with health services between patients using BPJS and other insurance users. Methods: The design used in this study was Cross Sectional. The total sample size is 80, namely 40 BPJS patients and 40 non BPJS patients with purposive sampling technique. The research variables consisted of: the level of patient satisfaction (dependent) and health services (independent). The questionnaire on the level of patient satisfaction and health services uses an instrument that has been developed by the management of Adi Husada Kapasari Hospital. Data were analyzed by Spearman rank correlation and Chi-square test with a significance level of 0.05. Results: The results showed BPJS patients were not satisfied (25%) and satisfied (25%) towards health services. However, non -BPJS patients are mostly satisfied (35%) for health services. This is because the entire staffing status of health workers has become a permanent employee, and the length of work of health workers has been 2-3 years so that health services to BPJS and Non BPJS patients do not look at the patient's status, all patients are treated equally in providing health services. Conclusion: Adi Husada Kapasari Hospital is expected to continue to provide quality and satisfying health services to patients regardless of insurance participants. Improving the quality of health services to always be developed following the development of science in the health sector.